EVALUATION OF AGROFORESTRY SYSTEMS AS ALTERNATIVES FOR TIMBER PRODUCTION AND CARBON STORAGE - Israel Luiz de Lima; Maurício Ranzini; Maria Luiza Franceschi Nicodemo; Eduardo Luiz Longui (Revista do Instituto Florestal)
- In Agrossilvipastoril systems trees are cultivated together with agricultural crops or animals, aiming at multiple uses therefore constituting a viable option for better soil use. Thus, reversing the processes of degradation of natural resources, to increase the availability of wood, food and environmental services and emerging as a sustainable alternative to the currently used wood production systems. Here we investigate the effect of the Silvi-agricultural and Silvi-pastoral systems on dendrometric data, mean annual increment (MAI), CO2 sequestration, wood density and anatomical features of Croton floribundus and Guazuma ulmifolia trees. The highest values of DBH (1.3 m from the ground), tree volume, volume per ha and MAI were observed in the silvi-agricultural system. Among the systems, C. floribundus presented higher values compared to G. ulmifolia in the silvi-agricultural system. While in the silvi-pastoral system, greater DBH and consequently greater volume of trees, volume per ha and MAI occurred in G. ulmifolia when compared to C. floribundus. CO2 sequestration values corroborated the MAI, with higher values in the silvi-agricultural system. Wood properties are affected in part by the type of system. C. floribundus has lower wood density values and higher vessel element length values, regardless of the management system, and the reverse occurs for G. ulmifolia. In this study, we demonstrated that integrating short-cycle crop cultivation with timber tree production is a feasible approach, which not only enhances carbon storage but also aligns with Environmental, Social, and Governance (ESG) criteria. These findings highlight that agroforestry systems not only enhance timber production but also diversify farmers' income streams and make a significant contribution to carbon sequestration, establishing themselves as a sustainable and economically viable land management solution.